Mechanistic Studies on the Reactions of Dialkoxycarbenes with Carbonyl Compounds - Pole, David L. (My University, 1996)
Syntheses of 2.2-dimethoxy-5,5-dimethyl-Δ³-1,3,4-oxadiazoline (51) were performed from either lead (IV) acetate or iodobenzene diacetate oxidation of the carbomethoxy hydrazone of acetone (200) in methanol. The synthesis of 2-acetoxy-2 methoxy-5,5-dimethyl-Δ³-1,3,4-oxadiazoline (207) was achieved by lead (IV) acetate oxidation in dichloromethane solvent. The synthesis of 51 from substitution by methanol on 2-acetoxy-2-methoxy-5,5-dimethyl-Δ³-1,3,4-oxadiazoline (207) was also performed. Synthesis of 2-methoxy-5.5-dimethyl-2-(2,2.2-trifluoroethoxy)-Δ³-1,3,4-oxadiazoline (210) was achieved by substitution by 2.2,2-trifluoroethanol on 2-acetoxy-2-methoxy-5,5-dimethyl-Δ³-1,3,4-oxadiazoline (207).
Thermolyses of 51 and 210 in the presence of a variety of cyclic anhydrides 215 yield the products 216. Dialkoxycarbene reactions with unsymmetrically substituted anhydrides have been shown to occur preferentially at the most electron deficient carbonyl group. Competition studies between substituted maleic anhydrides show a preference for carbene attack on the most electron deficient anhydride. On the basis of these studies, the mechanism for the formation of 216 is believed to occur by inital attack of the dialkoxycarbene onto the carbonyl group of the anhydride.
Thermolyses of 51 and 210 in the presence of benzoyl cyanide 122b and benzoyl fluoride 122c were found to yield the products 127b-e. The mechanism of formation of these compounds was also attributed to initial attack of dialkoxycarbene onto the carbonyl group. In keeping with literature results, dimethoxyoxadiazoline 51 was found to react with benzoyl chloride (122a) to yield methyl benzoylformate (125). Thermolysis of 51 in the presence of benzalphthalide (224) was found to yield the product 225. The results are discussed in terms of the mechanism of the 1.2-group migration common to all these reactions and those of dialkoxycarbene addition to anhydrides.
Reaction of 51 with 9-fluorenone (230) and coumarin (231) yield products from intramolecular methoxy migration. The mechanism was established by deuterium and ¹⁸O labelling experiments. This mechanism involves the intermediacy of an oxirane 235. Although 235 can be identified in the reaction mixture after shortened thermolysis times it does not survive attempts at isolation.
N-Phenylmaleimide (270) was found to intercept dimethoxycarbene (10) to give a cyclopropane product 271. The regiochemistry of addition to maleimide and maleic anhydride was examined by ab initio molecular orbital calculations. The computational results reflect the observed sense of regioselectivity only when higher level basis sets employing polarization functions are used to calculate the energies.
Thermolyses of 51 and 210 in the presence of the stable 1,2-bisketene 292 yielded products of overall [4 + 1] addition of the dialkoxycarbene to the π-system of the bisketene. This result is in keeping with dialkoxycarbene addition to the less hindered side of the bisketene.
Thermolyses of dimethoxyoxadiazoline 51 in the presence of β-dicarbonyl compounds 302a-d yield the products of formal insertion of the carbene into the C-H bond of the keto tautomer. The presence of the enol tautomers of these compounds is expected to be substantial on the basis of literature values for the equilibrium constants in benzene. The results indicate that the reaction is likely to proceed through O-H insertion of the dialkoxycarbene through an ion pair intermediate. This is fitting for the mechanism of O-H insertion for nucleophilic carbenes.
Keywords: Chemistry; Chemistry